Proteome research : new frontiers in functional genomics - Wilkins, M. R; Appel, R. D; Wikins, M. R; Williams, K. L (Springer, 1997)
Recent advances in two-dimensional electrophoresis, protein microanalysis and bioinformatics have made the large-scale, systematic analysis of proteins and their post-translational modifications from any tissue or organism possible. This approach has acquired the name \"Proteome Research\", and can be considered as the core of functional genomics. The results of proteome analysis show which genes are expressed, how the protein products are modified, and how they interact, making proteome research of fundamental importance for the biologist, clinician, and pharmaceutical industry.
Principles and practice
Keywords: Genome; genetika, lékařská genetika; Genetics; genetika; genom lidský; Genome, Human; genom; Proteom